Allocation of governmental authority and responsibility in Tiered governance regimes: the case of the Chivi rural district council landuse planning and conservation by-laws - Mandondo, A. (2001)
The proper alignment of authority and responsibility within and between various levels of social organization is a fundamental governance problem. This study uses a review approach to critically interrogate the political economy of the allocation of environmental jurisdictions between the state, local communities and Rural District Councils in Zimbabwe. Rural District Councils have the authority to enact conservation and landuse planning by-laws. A subsidiary aim is to investigate the practical operation of these by-laws in everyday social life through analysis that situates the effectiveness of by-laws within the theme of proximity to citizens. Several flaws and contradictions are evident in the political economy of the allocation of authority and responsibility among these actors. Assignment of responsibilities is framed by a top-down structure in which entrustments are transferred solely to Rural District Councils at the expense of other levels of social organization, particularly those close to the citizens. Governance arrangements fostered through the by-laws punish citizens for not respecting arrangements that they do not effectively participate in crafting. Revenues accruing from fines imposed on people violating such arrangements accrue to the Rural District Councils, not to the communities from which they are extracted. The study argues for innovative governance approaches that entail fundamental changes in by-law articulation.